1942
DOI: 10.1172/jci101285
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Diet on the Ascorbic Acid Requirement of Premature Infants

Abstract: The purpose of this report is to present data, obtained on premature infants, demonstrating that one of the factors determining the need for ascorbic acid is the level of protein intake. It is proposed that this factor plays a role in the greater requirement of artificially fed babies, as compared to breast-fed infants, for supplements containing this vitamin.Long before actual data were available as to the daily total ascorbic acid requirement of the newborn infant, or as to the amount of the vitamin present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1942
1942
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…They found five preterm infants who excreted hydroxphenyl compounds. The urinary levels of these compounds were markedly reduced by large doses (25-200 mg) of parenterally administered vitamin C. In an unpublished survey of 15,000 infants referred to by Avery et al (1967), tyrosinemia and tyrosyluria were more prevalent in preterm infants (30%) than in term infants (10%), and diets high in protein were associated with an increased incidence (Dann, 1942;Levine et al, 1941;Woolf & Edmunds, 1950). In addition, smaller preterm infants were reported to have a higher incidence of tyrosinemia than larger ones (Light et al, 1966), 41% compared with 22%.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…They found five preterm infants who excreted hydroxphenyl compounds. The urinary levels of these compounds were markedly reduced by large doses (25-200 mg) of parenterally administered vitamin C. In an unpublished survey of 15,000 infants referred to by Avery et al (1967), tyrosinemia and tyrosyluria were more prevalent in preterm infants (30%) than in term infants (10%), and diets high in protein were associated with an increased incidence (Dann, 1942;Levine et al, 1941;Woolf & Edmunds, 1950). In addition, smaller preterm infants were reported to have a higher incidence of tyrosinemia than larger ones (Light et al, 1966), 41% compared with 22%.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…There are conflicting reports, especially in the earlier literature, concerning the need for higher vitamin C intakes to prevent or alleviate tyrosinemia of prematurity (Avery et al, 1967;Dann, 1942;Levine et al, 1939;Light et al, 1966;Mathews & Partington, 1964;Woolf & Edmunds, 1950). Levine et al (1939) reported that high doses of parenteral vitamin C, up to 200 mg/single dose, in a total of 525 mg during a 4-day period, given to five premature infants fed dried cow milk without added vitamins C or B, resulted in a rapid decline in urinary tyrosine as measured by the Millon reaction.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…She found that infants on high protein diets developed lower plasma concentrations of ascorbic acid. 13 Premature infants particularly are prone to develop rickets. Customary explanations include initially low body stores of calcium and phosphorus, rapid rate of growth, faulty absorption of fat-soluble vitamin D, and prolonged shelter from exposure to sunlight.…”
Section: Effect Of Protein Intake On Growthmentioning
confidence: 99%
“…The ascorbic acid requirements of premature infants 77 and school children 7S have been reported, and it has been shown rather definitely that children who receive 3 ounces (90 cc.) or more of orange juice daily or an equivalent amount of ascorbic acid in citrus fruits and tomatoes maintain a liberal level of ascorbic acid in the plasma.79…”
Section: Ascorbic Acidmentioning
confidence: 99%